2019
DOI: 10.1128/mbio.00089-19
|View full text |Cite
|
Sign up to set email alerts
|

A Klebsiella pneumoniae Regulatory Mutant Has Reduced Capsule Expression but Retains Hypermucoviscosity

Abstract: The polysaccharide capsule is an essential virulence factor for Klebsiella pneumoniae in both community-acquired hypervirulent strains as well as health care-associated classical strains that are posing significant challenges due to multidrug resistance. Capsule production is known to be transcriptionally regulated by a number of proteins, but very little is known about how these proteins collectively control capsule production. RmpA and RcsB are two known regulators of capsule gene expression, and RmpA is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
140
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(169 citation statements)
references
References 35 publications
14
140
1
Order By: Relevance
“…The hmv of hvKp is generally ascribed to increased production of CPS; however, recent studies have challenged this paradigm [24–27, 30]. This paradigm shift in our understanding of K. pneumoniae hmv has been an emerging concept in recent years as genes, namely kvrA, kvrB, rmpC , and rmpD , have been identified that differentially affect hmv and CPS biosynthesis [17, 25, 26, 30]. Here, we have generated a condensed, ordered transposon library in a genetically tractable and hmv strain of K. pneumoniae , KPPR1, and used this library to query a question at the forefront of K. pneumoniae pathogenesis, namely, how do hmv and CPS biosynthesis independently and coordinately impact invasive hvKp infections?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hmv of hvKp is generally ascribed to increased production of CPS; however, recent studies have challenged this paradigm [24–27, 30]. This paradigm shift in our understanding of K. pneumoniae hmv has been an emerging concept in recent years as genes, namely kvrA, kvrB, rmpC , and rmpD , have been identified that differentially affect hmv and CPS biosynthesis [17, 25, 26, 30]. Here, we have generated a condensed, ordered transposon library in a genetically tractable and hmv strain of K. pneumoniae , KPPR1, and used this library to query a question at the forefront of K. pneumoniae pathogenesis, namely, how do hmv and CPS biosynthesis independently and coordinately impact invasive hvKp infections?…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ability of the bacteria to distinctly control hmv and CPS biosynthesis suggest that there are environmental conditions in which one or both properties are advantageous, emphasizing that while these two features are closely associated with hypervirulent K. pneumoniae , they likely serve distinct functions within specific environments and may actually be regulated in response to the local environment [39]. For example, the hmv low /CPS WT Δ rmpD mutant adheres to macrophage-like J774A.1 cells more than WT, while the hmv WT /CPS low Δ rmpC mutant adheres similar to WT [25, 26]. In addition, non-mucoid strains are more likely to be isolated from urine than blood [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst RmpA appears to coordinate capsule and HMV, RmpC only regulates capsule; an rmpC mutant synthesizes less capsule, but retains hypermucoviscosity. This suggests that capsule synthesis is not required for the HMV phenotype [121]. Indeed, early reports of RmpA and RmpB proposed that capsule overexpression was not the basis for HMV [105,115].…”
Section: Defining Hvkphypermucoviscositymentioning
confidence: 97%
“…DhaR is a transcriptional activator responsible for controlling the production of the metabolic enzymes glycerol dehydrogenase and dihydroxyacetone kinase (18,19). KvrA is a MarR-type transcriptional repressor with a key role in K. pneumoniae capsulation (2022).…”
Section: Textmentioning
confidence: 99%